2016
DOI: 10.1002/jbm.b.33791
|View full text |Cite
|
Sign up to set email alerts
|

Engineering anisotropic biphasic Janus‐type polymer nanofiber scaffold networks via centrifugal jet spinning

Abstract: Biphasic materials, comprised of an ordered arrangement of two different material phases within a material, have the potential for a wide variety of applications including filtration, protective clothing and tissue engineering. This study reports for the first time, a process for engineering biphasic Janus-type polymeric nanofiber (BJPNF) networks via the centrifugal jet spinning technique. BJPNF alignment and fiber diameter was dependent on fabrication rotational speed as well as solution composition. The bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…Janus membranes can be obtained by either asymmetric fabrication or asymmetric modification. Asymmetric fabrication includes integrating double layers through sequential electrospinning, filtration, or directly compositing ready‐made layers into a membrane . Only a limited number of materials are readily available by this method, such as nanofibers, nanowires, and carbon nanotubes .…”
Section: Introducing Asymmetry Into Membranesmentioning
confidence: 99%
“…Janus membranes can be obtained by either asymmetric fabrication or asymmetric modification. Asymmetric fabrication includes integrating double layers through sequential electrospinning, filtration, or directly compositing ready‐made layers into a membrane . Only a limited number of materials are readily available by this method, such as nanofibers, nanowires, and carbon nanotubes .…”
Section: Introducing Asymmetry Into Membranesmentioning
confidence: 99%
“…[3][4][5][6] These excellent water harvesting creatures elucidate the critical role of wettability irregularity and hierarchical structure gradient in guiding water transport. [23][24][25][26][27][28][29][30] Our previous works have reported the preparation of hydrophobic-to-hydrophilic gradient fabrics that can guide directional water-transport from the hydrophobic to the hydrophilic side. [19][20][21][22] However, most of the water harvesters developed so far are based on either a 2D surface or a 1D filament.…”
mentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30] Our previous works have reported the preparation of hydrophobic-to-hydrophilic gradient fabrics that can guide directional water-transport from the hydrophobic to the hydrophilic side. [23][24][25][26][27][28][29][30] Our previous works have reported the preparation of hydrophobic-to-hydrophilic gradient fabrics that can guide directional water-transport from the hydrophobic to the hydrophilic side.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that heart valve leaflet tissues have an intricate, heterogeneous, and multilayered structure that plays important roles in homeostatic maintenance and adaptive valvular remodeling. 19,21,24,75,[90][91][92][93] On the other hand, we have extensively demonstrated that a detailed account of the extracellular matrix composition or fiber architecture are not essential to obtain a faithful description of MV closure and accurate strains across the leaflet surface. 20,60,77 In addition, although the MV anterior belly region is highly anisotropic, 74,90 a large majority of the leaflet surface consists of smooth transition zones between adjacent MVCT insertion sites, and these regions have been shown to exhibit minimal anisotropy.…”
Section: Insights Into MV Mechanics and Functionmentioning
confidence: 99%